Parental Problems in Shaping Children’s Character in Lepo-Lepo Village, Baruga District, Kendari City - Marlina; Musthan, Zulkifli; Sufiani, Sufiani; Rasmi (Dirasah: Jurnal Pendidikan Islam, 2026)
The aim of this research is to find out the character of children in Lepo-Lepo Village, Baruga District, Kendari City, to find out the problems of parents in shaping children's character in Lepo-Lepo Village, Baruga District, Kendari City. This type of research is descriptive qualitative research. It is hoped that the benefits of this research will provide benefits both theoretically and practically, as well as being beneficial for children and also for researchers. The data collection techniques used were observation, interviews and documentation. The data analysis technique is carried out based on descriptive analysis, namely data collection, data reduction, data presentation and drawing conclusions. The results of the research show that: (1) Children's character traits are affected by bad company, including some children who have tried smoking and are less polite to their parents because they like to fight or argue with their parents, interrupt conversations when someone is talking, lie, and children like to say harsh things with their friends. (2) The problems of parents in forming children's character include the child's lack of awareness of advice from their parents, lack of togetherness between parents and children because parents are busy working, often play games, environmental influences that make children like to lie and say harsh things.